The effect of the shaw English online channel on the EFL students’ speaking ability - Riswanto Riswanto; Anita Anita; Kasmaini Kasmaini; Anisa Imelda (JOALL (Journal of Applied Linguistics and Literature), 2022)
This study aims to investigate whether or not the learning strategy using YouTube videos from the Shaw English Online Channel is effective on students' speaking skills in asking questions and giving opinions. This research was conducted at Islamic Senior High School 2 North Bengkulu.  The method applied in this research was quantitative with a quasi-experimental design.  The total sample used for this study was 70 students consisting of 35 students from the eleventh grade of natural sciences class 1 (experimental class) and 35 students from the class eleventh grade of natural sciences class 2 (control class).  The instrument in this study was an online oral test and the data was the students' pre-test and post-test scores which were calculated and analyzed using SPSS 26 software. Then, the results obtained were used to determine whether there was an effect given by variable x to variable v. In conclusion, the use of learning strategies using media from the Shaw English Online Channel is effective to improve students' speaking skills in asking questions and giving opinions to eleventh-grade sciences students at Islamic Senior High School 2 North Bengkulu, the academic year 2021.